606 Oral anticoagulants in fragile patients with percutaneous endoscopic gastrostomy and atrial fibrillation: the Origami study. (17th December 2020) - Arcudi, Alessandra; D'Amario, Domenico; Galli, Mattia; Canonico, Francesco; Restivo, Attilio; Scacciavillani, Roberto; Cappannoli, Luigi; Riccioni, Maria Elena; Annetta, Maria Giuseppina; Di Stefano, Gaetano; Piccinni, Carlo; Vergallo, Rocco; et al.
Abstract: Aims: Randomized trials support the safety and efficacy of direct oral anticoagulants (DOACs) vs. vitamin K antagonists (VKA) in patients with nonvalvular atrial fibrillation (AF), leading to increased use of these compounds. Crushed forms of DOACs have shown to be reliable, but evidence supporting percutaneous endoscopic gastrostomy (PEG) delivery is lacking. PEG is a long-term option for enteral food and drug delivery in patients unable to maintain oral intake, bypassing the risks and disadvantages of parenteral nutrition. We investigate the safety and efficacy of Edoxaban administered via PEG in patients with atrial fibrillation and a clinical indication for a long-term anticoagulation. Methods and results: In this prospective, single centre observational study, 12 PEG-treated patients with indication to anticoagulation will receive edoxaban via PEG and will be followed-up to 6 months. Plasma anti-Factor Xa activity and edoxaban concentrations will be assessed. Thromboembolic (ischaemic stroke, systemic embolism, venous thromboembolism) and bleeding events (Bleeding Academic Research Consortium and Thrombolysis in Myocardial Infarction) will be recorded at 1 and 6 months. A retrospective analysis of 5 AF cases undergoing PEG-implantation at our Institution, who received edoxaban via PEG, showed plasma anti-FXa levels at steady state of 146 ± 15 ng/ml, without major adverse event at a mean follow-up of 6 months. Conclusion: We prospectively investigate PEG-administration of edoxaban in PEG-treated patients requiring long term anticoagulation. Our preliminary retrospective data support this route of DOAC administration.